2024
DOI: 10.3390/pharmaceutics16040440
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Hybrid Vesicles and Cellular Internalization in Mammary Cancer Cells

So Yun Kim,
Dagyeong Guk,
Youngdo Jeong
et al.

Abstract: Extracellular vesicles play an important role in intercellular communication, with the potential to serve as biomaterials for nanocarriers. Combining such extracellular vesicles and liposomes results in advanced drug delivery carriers. In this study, we attempted to fabricate hybrid vesicles using a membrane fusion method and incorporated an anticancer drug. As a result, we successfully prepared nanosized uniform hybrid vesicles and evaluated their physicochemical characteristics and intracellular uptake mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In this study, pegylated pH-sensitive liposomes fused with EVs isolated from human breast cancer cells (MDA-MB-231) were prepared by the film hydration method [ 10 ]. Kim and Evers used a similar method, hydrating the lipid film with an EV-containing aqueous solution [ 20 , 21 ]. Another study by Hu et al promoted the fusion of EVs and liposomes using different methods, such as incubation followed by extrusion [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, pegylated pH-sensitive liposomes fused with EVs isolated from human breast cancer cells (MDA-MB-231) were prepared by the film hydration method [ 10 ]. Kim and Evers used a similar method, hydrating the lipid film with an EV-containing aqueous solution [ 20 , 21 ]. Another study by Hu et al promoted the fusion of EVs and liposomes using different methods, such as incubation followed by extrusion [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study of cellular DOX uptake also showed that the association of EVs in the lipid bilayer did not prevent DOX uptake by breast cancer cell lines. Kim and Evers [ 20 , 21 ] showed that the EV:liposome particle proportion alters some physicochemical properties and cellular uptake of the bioactive substance encapsulated. Evers showed that the cellular uptake of hybrid formulations was enhanced in the 1:50 EV:liposome proportion compared to the 1:100 EV:liposome proportion [ 21 ].…”
Section: Discussionmentioning
confidence: 99%